Rheological behavior and antiarthritic activity of Pterodon pubescens nanoemulsion (Research, Society and Development, 2020)
Pterodon pubescens, popularly known as "sucupira", it is traditionally used as anti-inflammatory agent. This work aimed to evaluate the in vivo antiarthritic properties of a P. pubescens oil nanoemulsion and the rheological behavior of the developed system. The viscoelastic properties, creep and recovery were evaluated by dynamic oscillatory tests. The antiarthritic activity of the nanoemulsion was evaluated by the zymozan-induced arthritis model, at three different doses (25, 50 and 125 mg/kg/day). P. pubescens oil nanoemulsion has been shown to decrease cell recruitment to a joint cavity and increased cartilaginous regeneration at the end of treatment of the dose of 50 mg/kg. The evaluation of the behaviour of deformation allowed to observe that the P. pubescens nanoemulsion presents predominantly elastic characteristic. These findings demonstrate the potential of P. pubescens and nanotechnology in the development of new antiarthritic drugs.